Micrasterias crux-melitensis Ehrenberg var. multispinosa W.W.A.Kow. var. nov. and Xanthidium fasciculatum Ehrenberg ex Ralfs var. burchardtii W.W.A.Kow. var. nov. – new taxa for the desmidia flora from wetland ecosystems of Western Pomerania, Poland - Kowalski, Wojciech W. A. (Annales Universitatis Paedagogicae Cracoviensis Studia Naturae, 2024)
The paper presents the characteristics and description along with the original drawings of two taxa of the order Desmidiales (Chlorophyceae) that have not been recorded in the world so far. They belong to the species Micrasterias crux-melitensis Ehrenberg ex Ralfs and the species Xanthidium fasciculatum Ehrenberg. The found specimens are characterised by different morphological features, which have not been recorded in the descriptions of forms and typical varieties representing these genera in the world flora. Single cells of those varieties were present in the materials collected during fieldwork carried out as part of the reconnaissance and registration of phycoflora habitats of moss bog ecosystems in Western Pomerania.